BIOETHICS IN MODERN SOCIETY - Лесін, А. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The main aim in relations between doctor and patient are positive achievement in concrete process of medical treatment in which for sexual pathological profile patient are interaction in triumvirate: doctor – professional – patient – his rational sexapil Medicine and doctors are judged by medical treatment results, but it is necessary to keep healthy lifestyle in all its aspects. Owing to scientific progress, compulsory professionalism reduce mistakes in medical treatment.